Arthroscopic capsular release for the treatment of post-stroke frozen shoulder: A protocol for systematic review. Issue 39 (25th September 2020) - Zong, Long-ze; Ma, Li; Liu, Ying-ying
Abstract: Background: This study will assess the efficacy and safety of arthroscopic capsular release (ACR) for the treatment of post-stroke frozen shoulder (PSFS). Methods: We will carry out a systematic study of randomized controlled trials that assess the efficacy and safety of ACR for PSFS. We will search all potential records for any eligible trials from selected electronic databases (MEDLINE, EMBASE, Cochrane Library, Web of Science, Chinese Biomedical Literature Database, WANGFANG, and China National Knowledge Infrastructure) and grey literature sources from inception to the present. Two authors will independently perform study selection, data extraction, and study quality assessment. Any disagreement will be solved by a third author via consultation. Statistical analysis will be carried out by RevMan 5.3 software. Results: This study will comprehensively summarize current eligible studies to systematically assess the efficacy and safety of ACR for PSFS. Conclusion: This study will provide evidence to determine whether ACR is an effective management for patients with PSFS.